Factors Influencing Supportive Care Needs of Colorectal Cancer Survivors - Hyekyung Kim; Yang-Sook Yoo (Elsevier, 2021)
Summary: Purpose: There is an increasing number of colorectal cancer survivors in South Korea. However, no research has identified supportive care needs of survivors of colorectal cancer in South Korea. Thus, the purpose of this study was to determine the level of supportive care needs and effects of emotional state and quality of life (QoL) on supportive care needs of colorectal cancer survivors. Methods: This cross-sectional study was conducted among 115 survivors of colorectal cancer in South Korean who had primary treatment of surgery for colorectal cancer. Data were collected from April to September 2016. Participants responded to self-reported questionnaires assessing supportive care needs, emotional state (Hospital Anxiety and Depression Scale), and QoL (Functional Assessment of Cancer Therapy-Colorectal scale). Results: The overall score of supportive care needs for colorectal cancer survivors was 1.22 ± 0.61 (full score: 3 points), with health care staff and social support needs garnering highest scores. Approximately, 20.0% and 21.7% of patients had anxiety and depression, respectively. The mean QoL score was 2.90 ± 0.53, with social and family status having the lowest QoL score. Multiple regression analysis showed that both the period after treatment and anxiety significantly influenced supportive care needs. Conclusion: Appropriate interventions should be used immediately after completion of treatment to help reduce anxiety and meet supportive care needs of colorectal cancer survivors.